Marketing Strategy Throught Social Media to Incrase Customers Purchasing Decision on Sports Apparel Companies - Pradiza, Rachel Aulia; Fatoni, Muhad (Jurnal Porkes, 2023)
The aim of the research is to find out how the sportswear company's strategy is described in utilizing social media as a marketing tool so that purchasing decisions are created. The method used is descriptive qualitative. Data collection techniques are interviews, observation, documentation. Data validity includes credibility, transferability, dependability, and certainty. Data analysis techniques include data reduction, data presentation, conclusions and verification. The results of marketing through Instagram social media can improve purchasing decisions, companies can maintain product quality through key performance indicators so that they are specifically able to help achieve company operational targets in maintaining product quality by strengthening standard operating procedures as a guide or company steps in completing work. Monitoring or good supervision and responsibility between divisions can maintain the quality of the company's products. In conclusion, the success of a sportswear company in creating purchasing decisions through the strategy of a sportswear company utilizing social media such as creating interesting content and communicating well to potential customers has a significant influence on purchasing decisions.